Accounting for Volunteers: Enhancing Organizational Accountability and Legitimacy. (February 2020) - Tooley, Stuart; Hooks, Jill
Volunteers are mission-critical resources, and the ongoing ability of many nonprofit organizations to serve their constituencies is dependent on such contributed services. Utilizing an online questionnaire administered to coordinators of volunteers, the study investigates perceptions and practices in the Australian nonprofit sector in the reporting of volunteer contributions of services. We find ( N = 166) that although organizations place high value on volunteer contributions, the benefits and impact are rarely reported. The majority of respondents consider that a statement of volunteer contributions should be included alongside financial statements to give a more complete representation of organizational performance. This would enhance the accountability and legitimacy of the organization. No regulatory requirement to report and a lack of resources are cited as the predominate reasons for current nondisclosure. The findings support the need for a best practice model for recording and reporting volunteer contributions to recognize the significance of the resource.